Magnesium hydride protects against acetaminophen-induced acute kidney injury by inhibiting TXNIP/NLRP3/nf-κb pathway - Yachen Si; Lulu Liu; Yinyin Zhang; Hongxia Li; Tingting Zhao; Su Liu; Xuejun Sun; Jin Cheng; Hongtao Lu (Renal Failure)
Acetaminophen (APAP)-induced acute kidney injury (APAP-AKI) has turned into one of reasons for clinic obtained renal insufficiency. Magnesium hydride (MgH2), as a solid-state hydrogen source, might be potentially applied in clinical practice. The current study aimed to investigate the protective effect of MgH2 against APAP-AKI. The results showed that MgH2 improved renal function and histological injury in mice of APAP-AKI. MgH2 also had protective effects on APAP-induced cytotoxicity in HK-2 cells. In addition, the increased level of reactive oxygen species (ROS) and expressions of inflammatory cytokines (TNF-α and IL-1β) and pro-apoptotic factors (Bad, Bax, Caspase3, and CytC) induced by APAP were downregulated with MgH2 treatment. Furthermore, the expressions of molecules related to TXNIP/NLRP3/NF-κB pathway (TXNIP, NLRP3, NF-κB p65 and p-NF-κB p65) in renal tissues and HK-2 cells were enhanced by APAP overdose, which were reduced by MgH2 administration. Collectively, this study indicated that MgH2 protects against APAP-AKI by alleviating oxidative stress, inflammation and apoptosis via inhibition of TXNIP/NLRP3/NF-κB signaling pathway.